Evaluation of Impact of Overweight BMI, High Triglyceride, Total Cholesterol, Elevated SBP and High Pulse Rate on Cognitive Ability of Undergraduates Medical Students - Abdali, Ashraf; Shamalwal, Sayed Rahim Shah; Amal, Maghferatullah (Journal for Research in Applied Sciences and Biotechnology, 2024)
Introduction: Cognitive abilities have been the focus of behavior investigations for decades. Cognitive impairment share many common risk factors, such as hypertension, elevated cholesterol, hyperglycemia, and obesity are all associated with longitudinal declines in cognitive function and dementia. Several study’s analyzed the link between cholesterol levels and the development of dementia. Studys suggest that high levels of a specific sort of cholesterol (HDL) in blood wore associated with an increased risk of developing dementia. As well as high cholesterol also plays a role in the accumulation of amyloid beta peptides, which accelerates the development of cognitive impairment. We investigated correlation and impact of high TG, TC, Overweight BMI, Elevated SBP and High pulse rate on cognitive abilities from 386 participants on 59 top 10 undergraduate medical students. Objective: This study aimed to determine and evaluate the correlation and impact of high TG, TC, Overweight BMI, and Elevated SBP factors on cognitive abilities of top 10 undergraduated medical students in Ahmad Shah Abdali Higher Education Institute of Khost province of Afghanistan. Method and Materials: It is prospective descriptive cross sectional study, on 59 top 10 undergraduated medical students in Ahmad Shah Abdali Higher Education Institute of Khost province from 2023/ Oct / 12 to 2023/ Nov / 02. The including parameters were TG, TC, BMI, SBP and Pulse rate of all 386 participants under study that recorded in computer special format. TG, TC, BMI, SBP and Pulse rate are done by special regents, micro lab and cardiomonetor. Recorded findings processing, comparison and evaluation results have been identified by IBM SPSS-23 version. Results: The study was conducted during (20) days on 386 undergraduated medical students in Ahmad shah Abdali Higher Education Institute of Khost province. Initially we described all male participants according to age. At the current study all male participants were with (mean age: 23.14 ± 3.68; range: 20-45 years). All participants of this study were from all (1st, 2nd, 3rd, 4th, 5th and 6th) classes. Statistic description of all participants, according to TG, TC, BMI, SBP and Pulse rate shows that Normal healthy TG range˂150mg/dL: was more low 3(0.78%). Borderline TG = 150-199mg/dL; was more prevalent 306(79.27%) and High TG level =200-499mg/dL; was 77(19.94%). The normal healthy TC range˂150mg/dL: was more low 3(0.78%). Borderline TC = 150-199mg/dL; was more prevalent 306(79.27%) and High TC level =200-499mg/dL; was 77(19.94%). The Healthy weight range BMI= (18.5-24.9) was 219(56.74%). Overweight range BMI (25.0-29.9) was 114(29.53%). Obese range BMI≥ (30.0) was 29(7.51%) and underweight ˂18.5: was 23(5.96%). The normal SBP= (120-139mmHg) was 374(96.89%), Elevated SBP≥ (140 mmHg) was 12(3.11%). The normal range of pulse rate (60-100bpm) was 353(91.45%). Bradycardia˂ (60bpm) was 6(1.55%) and tachycardia> (100bpm) was 27(7.0%). In the second part of this study we described all above parameters in the group of all 59 top 10 participants students for comparative outcomes. Statistic description of 59 top 10 participants, according to Age, TG, TC, BMI, SBP and Pulse rate shows that at the current study top 10 participants were with (mean age 23.40± 2.78; range: 18-32 years). Normal healthy TG range˂150mg/dL: was 0(0%). Borderline TG = 150-199mg/dL; was more prevalent 54(91.53%) and High TG level =200-499mg/dL; was 5(8.47). The normal healthy TC range˂150mg/dL: was more prevalent 55(93.22%). Borderline TC = 150-199mg/dL; was low 4(6.78%) and High TC level =200-499mg/dL; was 0(0%). The Healthy weight range BMI= (18.5-24.9) was 33(55.93%). Overweight range BMI (25.0-29.9) was 18(30.51%), obese range BMI≥ (30.0) was 5(8.47%) and underweight ˂18.5: was 3(5.08%). The normal SBP= (120-139mmHg) was more prevalent 57(96.61%), Elevated SBP≥ (140 mmHg) was low 2(3.39%). The normal range of pulse rate (60-100bpm) was 49(83.05%).Bradycardia˂ (60bpm) was 1(1.69%) and tachycardia> (100bpm) was 9(15.25%). Pearson correlation between SBP and Weight is at the 0.01 level significant, (P<0.01). Pearson correlation between DBP and Pulse rate is at the 0.01 level significant, (P<0.00). Pearson correlation between TC and Weight is at the 0.05 level significant, (P<0.02). Pearson correlation between TG and Roll number is at the 0.01 level significant, (P<0.01). Pearson correlation between SBP and Roll number is at the 0.05 level significant, (P<0.04). Pearson correlation between Height and BMI is at the 0.01 level significant, (P=0.00). Pearson correlation between Weight and BMI is at the 0.01 level significant, (P=0.00). Pearson correlation between SBP and BMI is at the 0.01 level significant, (P=0.00). Conclusion: Overall, findings of our study indicated that, high TG, TC, Overweight range BMI, and elevated SBP have significant correlation with cognitive ability of undergraduated students. However, this issue needs to further investigations to confirm these findings.